All Days 2014
DOI: 10.4043/24819-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gas Hydrates Extraction by Swapping-Depressurisation Method

Abstract: Gas Hydrate, one of the unexplored domains in the energy sector has a vast potential to quench the future energy demands. Depressurization, Thermal Stimulation, Carbon swapping and Inhibitor injection are a few processes involved in its production. These techniques are environmentally degrading as uncontrolled dissociation of Gas Hydrates takes place. The paper focuses on an unexplored but a sustainable technique to extract gas hydrates. When depressurization along with CO 2 swapping methods are used simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Li S X et al [19] and Bai Y H et al [20] found through physical and numerical simulations, that although the combined method of heat injection and depressurization can effectively improve energy utilization, long-term depressurization may lead to reservoir instability. Gupta et al [21] found that the depressurization and CO 2 replacement method is efficient and economical, and can effectively solve the permeability problem, but this method must strictly limit the large amount of CO 2 overflow, so it has extremely high technical requirements and is not suitable for conventional mining. The combined method of depressurization and ground decomposition can easily cause formation instability due to the instability of shallow hydrate reservoirs on the seabed and the simultaneous action of pressure drop and shallow mining, so the mining efficiency of this method is low.…”
Section: Introductionmentioning
confidence: 99%
“…Li S X et al [19] and Bai Y H et al [20] found through physical and numerical simulations, that although the combined method of heat injection and depressurization can effectively improve energy utilization, long-term depressurization may lead to reservoir instability. Gupta et al [21] found that the depressurization and CO 2 replacement method is efficient and economical, and can effectively solve the permeability problem, but this method must strictly limit the large amount of CO 2 overflow, so it has extremely high technical requirements and is not suitable for conventional mining. The combined method of depressurization and ground decomposition can easily cause formation instability due to the instability of shallow hydrate reservoirs on the seabed and the simultaneous action of pressure drop and shallow mining, so the mining efficiency of this method is low.…”
Section: Introductionmentioning
confidence: 99%
“…Their research results showed that the replacement efficiency increased from approximately 64-85% (Kph et al, 2012). In practice, the above methods are combined to obtain better results, e.g., electric heating-assisted depressurization, CH 4 -CO 2 replacement-assisted depressurization, and co-injection of the inhibitor and CO 2 (Li et al, 2010;Gupta and Aggarwal 2014;Minagawa 2015;Khlebnikov et al, 2017). Accordingly, we propose a thermochemical reaction to utilize both the heat generated by a thermochemical reaction to provide heat for NGH decomposition and the gas generated by the thermochemical reaction to replace the methane in NGHs.…”
Section: Introductionmentioning
confidence: 99%